Regina Schulte: The Village in Court. Arson, Infanticide, and Poaching in the Court Records of Upper Bavaria, 1848-1910 - Knudsen, Anne (Tidsskriftet Antropologi, 2019)
Regina Schulte: The Village in Court. Arson, Infanticide, and Poaching in the Court Records of Upper Bavaria, 1848-1910 Anmeldes af Anne Knudsen